Pengawasan Jalur Kapal dengan Automatic Identification System (AIS) berbasis Android - Leonardo Yurion Tungribali; Justinus Andjarwirawan (Universitas Kristen Petra, 2022)
Indonesia, which is known as an archipelagic country, has a vast ocean that spans the country, that’s why Indonesia is known as a maritime country. With the vast sea, it becomes a wheel for economic turnover for Indonesia and internationally. Because Indonesia has 4 strategic points out of 10 points on international ship journeys, this makes Indonesian marine traffic very crowded and not a few ships from other countries cross Indonesian. When someone uses a ship to travel or deliver goods, there needs to be information about when the ship will arrive at its destination and the position of the ship when that person checks the information from the ship. Information about the ship consists of several important parts, the first is the estimated time of arrival (ETA), ETA is the time that ship will arrive at the port of destination, the second is the position of the vessel, the position of the vessel is in the form of latitude and longitude coordinates so that we can know the vessel's position on the map, and thirdly a ship specification that tells the ship type, ship size, MMSI, IMO, Call Sign, ship destination, and other important information. This information is quite difficult to find and also when looking for ETA the ship needs to go to the port and sometimes it is also not given in general at the port for certain vessels such as cargo and vessels other than passenger vessels. Therefore we need an application that can display ETA information, vessel position, and vessel specifications with the Android platform. The proposed application also has features that help users to do shipping or use transportation services using vessels. To obtain vessels information, an Automatic Identification System (AIS) is used which provides ship information and assists in calculating the vessel's ETA. ETA calculation and ship position prediction are assisted by the Haversine method. The results of the application have been tested with ETA information with test data, with the difference between ETA obtained from AIS and calculated by the system of ±20 minutes. The results of the application have been surveyed for the level of user satisfaction. The process of using the vessel is more helpful because of the features provided.